ANALISIS DAYA SAING KOMODITAS PERKEBUNAN DI KABUPATEN KAIMANA PROVINSI PAPUA BARAT - Suharyanto Suharyanto; Adang Agustian; Parlindungan Y Silitonga (Universitas Sebelas Maret, 2013)
Determination of superior regional commodity is the first step towards the agriculture development which based on concept of efficiency to achieve comparative and competitive advantage in the face of global trade.Step toward efficiency can be reached by developing commodity that has a comparative advantage in terms of both supply and demand side.The purpose of this study to analyzed the commodity which has the comparative advantage of various commodities that exist in the Kaimana district. Secondary data were collected on estate commodities production data sourced from BPS as well as primary data through a survey of 60 farmer respondents. Data analyzed using LQ (Location Quotient), Domestic Resources Cost Ratio (DRCR) and Private Cost Ratio (PCR). The analysis showed that the highest LQ value for coconut contained in Teluk Etnasub district, in the sub district Buruway cocoa and nutmeg in Kambrau sub district.Coconut, cocoa and nutmeg have a comparative advantage in Kaimana district as shown by DRCR smaller than one. While there is a competitive advantage only in cocoa and nutmeg demonstrated with PCR values smaller than one.